GOOD GOVERNANCE AND PUBLIC POLICY IN INDIA - Vedantham, V Mallika; Kamruddin, Shaik (PEOPLE: International Journal of Social Sciences, 2015)
Good Governance is required to ensure that the public policies have their desired effect. In the recent past, issues of governance have received serious attention from the researchers, policy makers and international development community. Today, ‘governance’ not only occupies centre stage in the development discourse but is also considered as a crucial element to be incorporated in the development strategy. The major focus of the study is on Good Governance and public policy process in India. In this context the present research paper discusses the basic concepts and elements of Good Governance in the first part of the article. The need of the Good Governance in the effective implementation of public policies has been elaborately discussed and the nature of public policy has been mentioned in the next part Various stages and constraints that are involved in public policy process and need for an effective policy has been discussed in detail in subsequent parts.